2021
DOI: 10.1002/nbm.4647
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics signature for temporal evolution and recurrence patterns of glioblastoma using multimodal magnetic resonance imaging

Abstract: Glioblastoma is a highly infiltrative neoplasm with a high propensity of recurrence. The location of recurrence usually cannot be anticipated and depends on various factors, including the surgical resection margins. Currently, radiation planning utilizes the hyperintense signal from T2‐FLAIR MRI and is delivered to a limited area defined by standardized guidelines. To this end, noninvasive early prediction and delineation of recurrence can aid in tailored targeted therapy, which may potentially delay the relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The authors reported an overall accuracy in the validation group (n = 20) of 0.78. In the study by Chougule et al [ 18 ] (2021), an accuracy of 0.71 was reported to predict local recurrence in the test group (n = 6). The authors trained a predictive recurrence model using voxel-based radiomic features of the T1ce, FLAIR, and ADC maps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported an overall accuracy in the validation group (n = 20) of 0.78. In the study by Chougule et al [ 18 ] (2021), an accuracy of 0.71 was reported to predict local recurrence in the test group (n = 6). The authors trained a predictive recurrence model using voxel-based radiomic features of the T1ce, FLAIR, and ADC maps.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to characterize tumor infiltration into the noncontrast-enhancing region through MRI and in combination with stereotactic biopsies [ 10 ] or by applying machine learning and deep learning models [ 11 , 12 , 13 , 14 ]. Moreover, several authors have proposed methods to predict regions of future tumor recurrence using MRI-based radiomic features [ 15 , 16 , 17 , 18 , 19 ]. Several of these studies show promising results, but they often require a great variability of image preprocessing, ground truth definitions, feature extraction, and data handling, as well as a need for advanced MRI sequences, which often hinder the generalization and applicability in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Multiparametric pattern analysis from clinical MRI sequences using radiomic signatures determined via machine learning methods has allowed the estimation of tumoral infiltration in NEPAs and the prediction of the rate and locations of tumor recurrence in HGG patients. The recurrent tumor region showed higher vascularity and cellularity as a radiomic signature [120][121][122][123][124]. Moreover, perfusion parameters for HGGs derived from DSC imaging have been used to determine four types of tumoral and peritumoral vascular heterogeneity based on CBV and CBF values: high-angiogenic and low-angiogenic regions of the enhancing tumor, potentially tumor-infiltrated peripheral edema and vasogenic edema.…”
Section: Correlation Between Nepas and Prognosismentioning
confidence: 99%
“…Glioblastoma (GBM) is the most common and aggressive primary brain tumor in adults (Chougule et al., 2022 ; Gonçalves et al., 2020 ), with high recurrence and mortality rates despite standard therapies (Campos et al., 2016 ; Parvaze et al., 2023 ). Molecular classification of GBM has been proposed to identify subtypes with distinct clinical, genetic, and epigenetic features for risk stratification (Gritsch et al., 2022 ; Yang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%